2021
DOI: 10.1002/anie.202112798
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Cooperative Catalysis for the On‐Surface Synthesis of Linear Heteroaromatic Polymers via Selective C–H Activation

Abstract: Regiospecific CÀ H activation is a promising approach to achieve extended polymers with tailored structures. While a recent on-surface synthetic approach has enabled regioselective homocoupling of heteroaromatic molecules, only small oligomers have been achieved. Herein, selective CÀ H activation for dehydrogenative CÀ C couplings of hexaazatriphenylene by Scholl reaction is reported for the first time. By combining low-temperature scanning tunneling microscopy (STM) and atomic force microscopy (AFM), we revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 51 publications
(84 reference statements)
1
18
0
Order By: Relevance
“…The organometallic DCA–Au–DCA structure is qualitatively different from previously observed 2D MOFs consisting of DCA molecules coordinated with metal atoms via their cyano groups. Moreover, the formation of the organometallic DCA–Au–DCA motif requires highly regioselective cleavage of the position A aromatic C–H bonds to enable the C–Au–C covalent bonding. Such C–H bonds have large dissociation enthalpies, ,, Δ H , meaning their cleavage seldom occurs at RT, and they often suffer from poor regioselectivity. ,,,, For a gas-phase DCA molecule for instance, we calculated Δ H values of 112.1 and 113.2 kcal/mol (4.86 and 4.91 eV) via DFT for the aromatic C–H bonds at positions A and B, respectively (see Figure a and SI Figure S7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The organometallic DCA–Au–DCA structure is qualitatively different from previously observed 2D MOFs consisting of DCA molecules coordinated with metal atoms via their cyano groups. Moreover, the formation of the organometallic DCA–Au–DCA motif requires highly regioselective cleavage of the position A aromatic C–H bonds to enable the C–Au–C covalent bonding. Such C–H bonds have large dissociation enthalpies, ,, Δ H , meaning their cleavage seldom occurs at RT, and they often suffer from poor regioselectivity. ,,,, For a gas-phase DCA molecule for instance, we calculated Δ H values of 112.1 and 113.2 kcal/mol (4.86 and 4.91 eV) via DFT for the aromatic C–H bonds at positions A and B, respectively (see Figure a and SI Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…52−58 Moreover, the formation of the organometallic DCA−Au−DCA motif requires highly regioselective cleavage of the position A aromatic C−H bonds to enable the C−Au−C covalent bonding. Such C−H bonds have large dissociation enthalpies, 60,68,69 ΔH, meaning their cleavage seldom occurs at RT, 70 and they often suffer from poor regioselectivity. 25,38,60,68,69 For a gas-phase DCA molecule for instance, we calculated ΔH values of 112.1 and 113.2 kcal/mol (4.86 and 4.91 eV) via DFT for the aromatic C−H bonds at positions A and B, respectively (see Figure 1a and SI Figure S7).…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In such QM/MM calculations, the molecule and Au adatoms were involved in the QM region, while the underlying surface was treated in the MM region. Previous studies [15,51] have shown that this QM/MM approach provides a reasonably accurate description of the chemical reactions involving adatoms.…”
Section: Forschungsartikelmentioning
confidence: 97%
“…Understanding the behaviour of the atomic halogen atoms in the molecular self-assembly may be beneficial to control the reaction pathway since a target coupling reaction can be induced with the reactants aligned by the halogen adatoms. 41,42 To the best of our knowledge, the condensation by the co-existing alkyl-alkyl interaction [43][44][45][46][47] and hydrogen bonding with dissociated bromine atoms 30,36 on the surface has not yet been investigated in detail under UHV at low temperature.…”
Section: Introductionmentioning
confidence: 99%